Forensic analysis of BiP Messenger on android smartphones - Akbal, Erhan; Baloglu, Ibrahim; Tuncer, Turker; Dogan, Sengul (Taylor & Francis Ltd, 2020)
Nowadays, social media applications and communication tools are utilized as communication platforms and the vast majority of communication is performed using these tools. The instant messaging applications have been widely used for peer to peer communication worldwide and BiP Messenger (BM) is one of them. BM has been generally used in Turkey. The BM was presented by Turkcell mobile GSM carrier offers many services such as messaging, video chatting, data transfer to smartphone users and approximately 10 million people have been used BM. Hence, it is one of the most encountered applications in forensics examinations. In this study, the BM is analysed using a mobile forensics methodology for the Android phones and this work presents the methodology of what artefacts produced by BM is, how to analyse them and how to show their relations with each other is presented. The proposed analysis methodology shows contact analyses, communication information, message information, deleted messages, group messages, message sending and receiving processes, the chronology of multimedia files and how to reconstruct them. The proposed methodology analysed data structure, communication protocols, permissions, user information, contact information, message information and log analyses of the BM.`wct 2Comprehensively mobile forensics examinations of BM were presented using these analyses in this paper.
Keywords: Mobile forensics; BiP Messenger; digital forensics; android OS; instant messaging